White spot lesions: diagnosis and treatment – a systematic review - Pedro C. Lopes; Teresa Carvalho; Ana T. P. C. Gomes; Nelio Veiga; Letícia Blanco; Maria José Correia; Anna Carolina Volpi Mello-Moura (BMC Oral Health, 2024)
Abstract Background White spot lesions represent the first stage of caries and their prevalence has been increasing in recent years, particularly in patients undergoing orthodontic treatment. DIferential diagnosis and lesion activity are essential to decide on the clinical approaches to treatment. The aim of this study is to understand if the new diagnostic tools such as fluorescence, microradiography and computed microtomography have the potential to change the conventional treatment of white spots”. Methods A systematic search of available studies in the literature was carried out, using PRISMA guidelines, in Pubmed and Scopus electronic databases and manually to identify relevant articles to answer the PICO question: “Do the new diagnostic tools have the potential to change the conventional treatment of white spots?”. This systematic review included randomized controlled trials (RCT), cross-sectional and longitudinal studies complying with the following inclusion criteria: (i) studies in humans, (ii) studies about white spot lesions, (iii) studies published between 2012 and 2023, (iv) studies having both diagnosis and treatment and (v) studies with full text available. In this review we excluded other systematic reviews of clinical trials and in vitro studies. The RoB tool was used to assess the risk of bias. Results The systematic literature search identified 143 potentially relevant references, which after applying the exclusion criteria, resulted in 20 articles. Regarding diagnostic methods, most articles found were based on conventional methods of visual examination (n:10) or fluorescence (n:7). The least referenced diagnostic techniques were based on the use of clinical photographs (n:2), cross-sectional microradiography (n:1) and computed microtomography (n:1). The use of DIAGNOdent was reported by 3 in vitro studies. With regard to therapies, most studies reported the use of infiltrating resin (n:7) and fluoride-based products (n:5). Other studies have reported the use of self-assembling peptide P11-4 (n:1), home care (n:1), casein phosphopeptide-amorphous calcium phosphate (n:2) and hydrochloric acid (n:1). Combination therapies were also considered. Conclusion Diagnostic tool does not have the potential to change the form of treatment, whether it is a conventional method or a more differentiated one.